2014
DOI: 10.5897/ajmr2013.5893
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of pure metals on clinically important bacteria growing in planktonic cultures and biofilms

Abstract: Antibiotic resistance in pathogenic bacteria is emerging as an issue of serious concern in bio-medical research as well as food and health organizations. Metal complexes are currently being employed in medical devices for their inhibition to bacterial adherence and antibacterial activities. The primary aim of this study was to evaluate the antibacterial activities of pure metals, including selenium, germanium and lithium on planktonic cultures and biofilms of three bacterial species: S. aureus SH1000, P aerugi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Antibiofilm agents like bismuth thiol and bismuth-ethane di thiol inhibits the biofilm formation of Staphylococcus aureus and methicillin resistant Staphylococcus epidermidis respectively [31]. On the other hand, pure metals, including selenium, germanium and lithium showed antibacterial activities on both planktonic and biofilms of three bacterial species: Staphylococcus aureus SH1000, Pseudomonas aeruginosa PA01 and Escherichia coli O157:H7 [32]. Gallium and Zinc convoluted with proto porphyrin IX (PP) or meso proto porphyrin IX (MP) was found to be effective against Staphylococcus aureus and Pseudomonas aeruginosa in planktonic as well as in biofilm form [33].…”
Section: Silver Shows Antibiofilm Activities Against Pseudomonas Aerumentioning
confidence: 99%
“…Antibiofilm agents like bismuth thiol and bismuth-ethane di thiol inhibits the biofilm formation of Staphylococcus aureus and methicillin resistant Staphylococcus epidermidis respectively [31]. On the other hand, pure metals, including selenium, germanium and lithium showed antibacterial activities on both planktonic and biofilms of three bacterial species: Staphylococcus aureus SH1000, Pseudomonas aeruginosa PA01 and Escherichia coli O157:H7 [32]. Gallium and Zinc convoluted with proto porphyrin IX (PP) or meso proto porphyrin IX (MP) was found to be effective against Staphylococcus aureus and Pseudomonas aeruginosa in planktonic as well as in biofilm form [33].…”
Section: Silver Shows Antibiofilm Activities Against Pseudomonas Aerumentioning
confidence: 99%
“…On the other hand, some DLC incorporation was shown to have no antibacterial effect contrarily DLC–Silicon (Si) coatings were claimed to enhance growth of E. coli cell culture 51 . Additionally, in different studies germanium element, nonionic surfactants, and organogermanium complexes were proposed that they have superior antibacterial properties on Gram negative, Gram positive and fungal cell cultures 52–54 . Our studies found that DLC–Ge coating samples exhibit good antibacterial activity for P. aeruginosa and it was determined that it reduced bacterial adhesion by 40% rate compared to the control.…”
Section: Resultsmentioning
confidence: 75%
“…The potential antibacterial properties of Ge compounds against human pathogenic bacteria have been previously demonstrated 19 . In addition, the antibacterial properties of Ge against P. aeruginosa planktonic and S. aureus have been demonstrated in suspension 20 . Ge is a dietary trace element necessary for some biological functions such as maintaining sodium, potassium, glucose, and pH values at normal levels, and lowering blood pressure 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The potential antimicrobial properties of Ge compounds were proved against the human pathogenic bacteria [9]. Also, the antimicrobial properties of elemental Ge have been shown in suspension against both Staphylococcus aureus and Pseudomonas aeruginosa planktonic [10]. Ge is a dietary trace element that is needed for some biological functions such as lowering blood pressure and maintaining the normal range of glucose, pH, sodium, and potassium [11].…”
Section: Introductionmentioning
confidence: 99%